State Civil Apparatus Services (ASN) In Management of Population Administration In Medan Johor sub-district, Medan City - Ivanna, Julia; Suherwani, Ella; Hodriani, Hodriani; Iqbal, Muhammad (PERSPEKTIF, 2020)
This study aims to determine the responsiveness of the State Civil Apparatus (ASN) serving the community in the administration of Population Administration at Medan Johor Sub-district office. The research method used is descriptive qualitative. The location of this research is Medan Johor Sub-district Office on Jln. Cipta No. 16 Pangkalan Mashhur, Medan Johor. Techniques of collection theÂ  data through observation, interviews and documentation. The data analysis technique carried out provides a clear picture of the research problem to be discussed and subsequently the data is presented qualitatively by reducing data, displaying data, and drawing conclusions. The results of this study indicate that the responsiveness of the State Civil Apparatus in the administration of population administration services in the Medan Johor Sub-district office has been going well. Related to responding to the applicant, speed, accuracy, accuracy, and responding to complaints, while regarding the timeliness indicators have not been implemented optimally. The supporting factor of responsiveness is in the form of a community that can listen well to the instructions of officers. Besides the inhibiting factors of responsiveness in the form of a network that is suddenly offline, people who do not want to be invited to cooperate, and the absence of printing machines in Medan Johor Sub-district office.